(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2025)
The populations of Mannia fragrans (Balb.) Frye & L. Clark in Haute-Loire, particularly at Blassac and Saint-Privat-d’Allier, are among the most demographically robust in Western Europe, with large population sizes and surface cover. This contrasts with marginal populations elsewhere, such as in Spain or Belgium. Unlike most European populations found on calcareous substrates, these occur on siliceous volcanic rocks. M. fragrans occupies transitional habitats between rocky outcrops and dry grasslands, where competition is limited and soil depth is sufficient. Dense bryophyte mats (e.g., Tortella squarrosa (Brid.) Limpr, Rhytidium rugosum (Hedw.) Kindb) and vascular competitors (e.g., Centaurea stoebe L.) restrict its development, particularly at Chilhac. The species thrives under harsh ecological conditions - steep slopes, shallow soils, and high rock cover - which limit plant competition. Its reproductive strategy is adapted to environmental variability, with spores released in spring and germination occurring in late summer, typically in microsites created by disturbances. Sporophyte abortion and rare germination events suggest constraints on sexual reproduction, though vegetative propagation is probably effective. Spatial distribution is patchy, conistent with by microtopographic factors and diaspores’ downslope movement via gravity and water runoff. These mechanisms promote local recolonization and delay succession. Conservation-wise, the Blassac population remains stable despite land abandonment, thanks to natural abiotic filters. Conversely, Chilhac shows signs of succession and competition, indicating a potential need for restored grazing. The spread of invasive Opuntia species, though limited for now, represents a latent threat. Continued monitoring and context-specific management may be required to preserve these rare liverwort habitats.